Empowering Advocates: Evaluating a Skill-Booster Intervention for Companions of Gender-Based and Child Violence Victims - Ifah Rofiqoh; Dian Yudhawati; Nuraini Aisiyah (Al-Qalam Institute, 2026)
Companions in cases of violence against women and children play an essential role in providing protection and recovery services for victims. This study aims to enhance companion capacity through a skill booster program focused on case management standards, victim-centred assessment, cross-agency coordination, and ethical gender-sensitive assistance. The program was implemented using a participatory capacity-building approach involving workshops, case studies, simulations, and focus group discussions. Evaluation used pre-test and post-test questionnaires, analysed with Respondent Achievement Level analysis. Results show an increase in mean score from 3.81 to 4.16, indicating improved competencies in case management understanding, victim assessment skills, and ethical practice implementation, while coordination across service networks remains limited. The findings imply that continuous capacity development is required to strengthen integrated service systems, improve inter-institutional collaboration, and enhance the professionalism and responsiveness of companions in handling violence cases against women and children. Strengthening referral mechanisms and periodic training is recommended to ensure sustainable service quality and effective victim protection outcomes at the institutional level through a continuous monitoring and evaluation system improvement cycle.